Failed peace in South Sudan? Exploring unarmed civilians and local peacekeepers through the work of nonviolent peaceforce - Muhammad Farid Abd Rahman; Owojori, Abimbola J.; Faridah Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2022)
Since the 2013 outbreak of civil war in South Sudan, the conflict has produced orgies of casualties and displacement of millions necessitating a series of mandates of the United Nations Mission in South Sudan (UNMISS). Yet, humanitarian crises and civilian protection challenges have not been reversed. To address these deficiencies, this article examined methods of the unarmed civilian peacekeeping as local peace formation and infrastructure involving the non-use of weapons for civilian protection as practiced by the Nonviolent Peaceforce (NP). Adopting ethnographic strands of Critical Peace Studies and utilisation of participant observations in humanitarian accounts with the NP between 2015 and 2019, our in-depth qualitative fieldwork indicates a potentially effective approach to unarmed civilian protection in the country. Our findings illuminate the limited viability of the UN civilian appointed personnel, while making an argument for the compelling efficacy of unarmed civilian peacekeepers in which those affected by the conflict are themselves empowered in their physical protection, the study further recommends the integration of the NP strategies into the current state of peace operation disarray so the current self-fulfilling prophecy of failed peace in South Sudan can be overturned.